Global Stability for the Cauchy Problem of a Class of Reaction-diffusion Systems (Journal of Partial Differential Equations, 2020)
By using invariant region argument together with Liapunov function technique for ODE, we give under certain circumstances a global stability analysis of the solutions for Cauchy problem of reaction-diffusion systems.
Keywords: Reaction-diffusion systems; Cauchy problem; global stability